1991
DOI: 10.1159/000281764
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Stained Structures in Prostatic Carcinoma: Evaluation of Diagnostic and Prognostic Relevance by Automated Image Analysis

Abstract: The comparison of the diagnostic and prognostic significance of histology, immunohistochemical parameters (PSA, PSP), and silver-stained nucleolar organizer regions (AgNORs) was estimated in paraffin sections taken of 63 prostatic carcinomas prior to therapy. AgNORs were visualized with a one-step silver staining technique with the appropiate staining time determined by preliminary staining-time series. The mean AgNOR number per cell (n) and the mean AgNOR area per silver-stained dot (A) were determined by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…However, the dif ference between poorly differentiated adenocarcinoma and M D A C was statistically not significant. Similar find ings have been reported earlier where the N O R counts increased up to grade 6 of Gleason's histological grade but not in tumours of grade 7 or more [13,14,20], The changes in the distribution of N ORs (number and size) reflect a different arrangement of actively transcribing D N A without notable changes in the total volume [21], Therefore, after a certain extent, the increase in NOR number is limited.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the dif ference between poorly differentiated adenocarcinoma and M D A C was statistically not significant. Similar find ings have been reported earlier where the N O R counts increased up to grade 6 of Gleason's histological grade but not in tumours of grade 7 or more [13,14,20], The changes in the distribution of N ORs (number and size) reflect a different arrangement of actively transcribing D N A without notable changes in the total volume [21], Therefore, after a certain extent, the increase in NOR number is limited.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the normal prostatic tissue and BPH sections had a mean N O R count of 2.87 ± 0.39 and 3.84 ± 0.40 NORs/nucleus, respectively, being slightly higher than the previously observed mean N O R count of 1.58 and 1.81 in normal prostatic tissue [12,13] and in BPH (1.72 NORs/nucleus) [14]. However, our finding compared favourably with the observations of some of the other workers where mean N O R counts in BPH were found to be 4.51 and 3.39, respectively [7,15], The mean N O R count in BPH with chronic prostatitis was 4.9 ± 0.55 which was significantly more (p < 0.05) than that seen in normal prostate and BPH without pros tatitis.…”
Section: Discussioncontrasting
confidence: 85%
“…6 The role of AgNOR is already well established in the diagnosis of oral cavity tumors, breast lesions, lymphoma and prostatic tumors. [7][8][9] However correlative studies of AgNOR staining with the cytomorphological features in FNAC of thyroid lesions are very few and inconsistent. 3 Hence in the present study, utility of AgNOR staining in FNAC smears of thyroid lesions is analyzed in the context of its use in differentiating benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor a is another polypeptide growth factor of 5.6 kD with a single chain of 50 amino acids [115] [ 143] found no ERBB2 expression in any of the prostatic carcinomas, whereas Ware et al [144] reported ERBB2 immunoreactivity in about 88% of prostatic carcinomas and in all hyperplasias. Also a recent study from 34 freshly frozen benign prostatic hyperplasias and 29 prostatic carcino mas showed that 18% of hyperplasias and 21 % of carcino mas were ERBB2 positive [ 134].…”
Section: Epidermal Growth Factor and Transformingmentioning
confidence: 99%